Case Report: Sudden death caused by methylene chloride poisoning - Shang, Ruikai; Tian, Qiaoxin; Liu, Yuru; Liu, Hongyu; Zhang, Xiangxing; Shi, Mengdi; Jian, Xiangdong; Li, Qilu (Frontiers in Pharmacology, 2024)
Dichloromethane is widely used as an organic solvent in aerospace, electronics, and medicine. Cases of poisoning caused by this substance are rare. Recently, we successfully treated a patient with an acute dichloromethane poisoning. During the production process, owing to pipeline leakage and lack of personal protection, the patient was poisoned by dichloromethane inhalation, fell from a height, and experienced a sudden cardiac arrest. After successful cardiopulmonary resuscitation, the patient was transferred to a local hospital for diagnosis and treatment and then to our hospital. After two visits to our hospital for systematic diagnosis and active treatment with fluid infusion, anti-infection therapy, glucocorticoids, ventilator-assisted respiration, chest strap fixation, and nutritional support, the patient achieved clinical recovery.